Shariah compliant credit cards: Disputes and steps forward / Zaimy Johana Johan. - Johan, Zaimy Johana (Universit Teknologi MARA Cawangan Selangor, 2019)
The major studies on Islamic credit card (ICC) started in 2011 until 2013 specifically examining operations and structures of ICC and behavioural studies. The other studies mostly explored and investigated behaviour and intention to utilise ICC. There are however, few studies comparing between ICC and conventional credit card (CCC) preference. On the same note, only a small number of studies have explored the importance of shariah compliance in influencing the behaviour of ICC adoption. Since shariah compliant credit cards are not popular as compared to the conventional ones, it is timely to review the breadth and depth of ICC studies in order to acknowledge the existence of the product in the market. Whether the product has been unattractive, lack of marketing and promotion from the bankers’ part or the public’s ignorance, insensitivity and unconsciousness about the products, the paper will provide an overview of the research work that has been conducted thus far. The studies on ICC are still limited in numbers and the focus areas are only skewed towards behaviour, satisfaction and the structure of the cards. The key features of ICC that differentiate the product with CCC still remain invisible and unnoticed. There is a critical need to further investigate another perspective of ICC by identifying the key features of shariah compliance and leverage on the benefits to consumers by protecting and preserving basic needs as well as promoting healthy banking environment.